The Role of Civic Education in Forming Character-Based Individuals in Elementary School Children - Agustina, Agustina; Nasution, Novita Sari; Adlani, Nazri (Yayasan Zia Salsabila, 2023)
This paper aims to find out and explain the role of civic education to form a person of character in elementary school children. The research method uses a qualitative study approach or a descriptive approach where the basis of the discussion is obtained from the results of literature studies on book sources, relevant journals that have existed before, and scientific articles. This study explains the role of Civics subjects in elementary schools in character building efforts. The results of this study indicate that Citizenship Education has an important role in shaping the character of students for the nation and the State to become better individuals. Citizenship Education in its teaching has a great impact on the character development of elementary school students. In Citizenship Education, students can learn to become human beings with good character and are responsible as citizens. This Citizenship Education must exist to create and grow young generations with character in the life of the nation and state for the betterment of the nation and the next generation.